LncRNA SNHG4 promotes osteosarcoma proliferation and migration by sponging miR‐377‐3p - Huang, Yi‐Feng (Mol Genet Genomic Med, 2020)
BACKGROUND: Long non‐coding RNAs (lncRNAs) have been identified as crucial regulatory factors in the occurrence and progression of osteosarcoma. METHODS: Quantitative real‐time polymerase chain reaction was used for detecting small nucleolar RNA host gene 4 (SNHG4) and miR‐377‐3p in osteosarcoma cells and tissues. Kaplan–Meier method was applied for evaluating the association between SNHG4 expression and the overall survival of osteosarcoma patients. CCK8, EdU, flow cytometry, and transwell assay were performed to examine the cell proliferation, apoptosis, cycle, and migration of osteosarcoma cells. RESULTS: In our study, we found that lncRNA SNHG4 was highly expressed in osteosarcoma tissues and cell lines. Additionally, the SNHG4 expression was related to distant metastasis, TNM stage, and survival of osteosarcoma patients. Through SNHG4 knockdown, the proliferation of osteosarcoma cells was considerably restrained and the cell apoptosis was induced in vivo and in vitro. Moreover, downregulated SNHG4 inhibited the cell migration and epithelial‐mesenchymal transition in HOS and MG63 cells. In mechanism, we found that SNHG4 acts as a competing endogenous RNA to sponge miR‐377‐3p, which is downregulated in osteosarcoma. Our results showed that there is a negative correlation between SNHG4 and miR‐377‐3p expression in osteosarcoma patients. CONCLUSION: Taken together, SNHG4 promotes cell proliferation and migration by sponging miR‐377‐3p in osteosarcoma.